Investigating the Consumer’s Perception on Selection of Mid Segment Cars by Students : A Conjoint Approach - Goyal, Amit; Shiva, Atul (Indian Journal of Marketing, 2016)
The aim of this article was to investigate the relationship between various attributes of mid segment cars and the selection of a best choice amongst them by the students. For this purpose, we examined different attributes affecting the buying behaviour decision making process of consumers represented by young students. The conjoint model was adopted and tested by panel data regression analysis for the formation of the best choice in selected attributes affecting the mid segment car purchase decisions. The data was collected from students of various colleges located in the District of Ludhiana in Punjab. The main results of this empirical research suggest that students preferred a petrol car with price which varied between INR 7-8 lacs having seating capacity of 7 people, horse power of the car varying between 1400-1500 cc, with fuel efficiency of 18-20 kmph with lower maintenance cost, which is lesser than INR 5000. The paper provides comprehensive empirical evidence about the selection of a particular mid segment car by the students and thus fills an important gap in the marketing literature which can be used by car manufacturers and distributors.